Effect of Pain Neuroscience Education Combined With Cognition-Targeted Motor Control Training on Chronic Spinal Pain: A Randomized Clinical Trial - Malfliet, Anneleen; Kregel, Jeroen; Coppieters, Iris; De Pauw, Robby; Meeus, Mira; Roussel, Nathalie; Cagnie, Barbara; Danneels, Lieven; Nijs, Jo (JAMA neurology, 2018)
Effective treatments for chronic spinal pain are essential to reduce the related high personal and socioeconomic costs. To compare pain neuroscience education combined with cognition-targeted motor control training with current best-evidence physiotherapy for reducing pain and improving functionality, gray matter morphologic features, and pain cognitions in individuals with chronic spinal pain. Multicenter randomized clinical trial conducted from January 1, 2014, to January 30, 2017, among 120 patients with chronic nonspecific spinal pain in 2 outpatient hospitals with follow-up at 3, 6, and 12 months. Participants were randomized into an experimental group (combined pain neuroscience education and cognition-targeted motor control training) and a control group (combining education on back and neck pain and general exercise therapy). Primary outcomes were pain (pressure pain thresholds, numeric rating scale, and central sensitization inventory) and function (pain disability index and mental health and physical health). There were 22 men and 38 women in the experimental group (mean [SD] age, 39.9 [12.0] years) and 25 men and 35 women in the control group (mean [SD] age, 40.5 [12.9] years). Participants in the experimental group experienced reduced pain (small to medium effect sizes): higher pressure pain thresholds at primary test site at 3 months (estimated marginal [EM] mean, 0.971; 95% CI, -0.028 to 1.970) and reduced central sensitization inventory scores at 6 months (EM mean, -5.684; 95% CI, -10.589 to -0.780) and 12 months (EM mean, -6.053; 95% CI, -10.781 to -1.324). They also experienced improved function (small to medium effect sizes): significant and clinically relevant reduction of disability at 3 months (EM mean, -5.113; 95% CI, -9.994 to -0.232), 6 months (EM mean, -6.351; 95% CI, -11.153 to -1.550), and 12 months (EM mean, -5.779; 95% CI, -10.340 to -1.217); better mental health at 6 months (EM mean, 36.496; 95% CI, 7.998-64.995); and better physical health at 3 months (EM mean, 39.263; 95% CI, 9.644-66.882), 6 months (EM mean, 53.007; 95% CI, 23.805-82.209), and 12 months (EM mean, 32.208; 95% CI, 2.402-62.014). Pain neuroscience education combined with cognition-targeted motor control training appears to be more effective than current best-evidence physiotherapy for improving pain, symptoms of central sensitization, disability, mental and physical functioning, and pain cognitions in individuals with chronic spinal pain. Significant clinical improvements without detectable changes in brain gray matter morphologic features calls into question the relevance of brain gray matter alterations in this population. clinicaltrials.gov Identifier: NCT02098005.